A New Heart-Cutting Method for a Multiplex Quantitative Analysis of Steroid Hormones in Plasma Using 2D-LC/MS/MS Technique - Kotasova, Marcela; Lacina, Ondrej; Springer, Drahomira; Sevcik, Jan; Brutvan, Tomas; Jezkova, Jana; Zima, Tomas (Molecules (Basel, Switzerland), 2023)
The aim of the current research was to develop a simple and rapid mass spectrometry-based assay for the determination of 15 steroid hormones in human plasma in a single run, which would be suitable for a routine practice setting. For this purpose, we designed a procedure based on the 2D-liquid chromatography-tandem mass spectrometry with a minimalistic sample pre-treatment. In our arrangement, the preparation of one sample takes only 10 min and can accommodate 40 samples per hour when tested in series. The following analytical run is 18 min long for all steroid hormones. In addition, we developed an independent analytical run for estradiol, significantly increasing the assay accuracy while taking an additional 10 min to perform an analytical run of a sample. The optimized method was applied to a set of human plasma samples, including chylous. Our results indicate the linearity of the method for all steroid hormones with squared regression coefficients R2 ≥ 0.995, within-run and between-run precision (RSD < 6.4%), and an accuracy of 92.9% to 106.2%. The absolute recovery for each analyzed steroid hormone ranged between 101.6% and 116.5%. The method detection limit for 15 steroid hormones ranged between 0.008 nmol/L (2.88 pg/mL) for aldosterone and 0.873 nmol/L (0.252 ng/mL) for DHEA. For all the analytes, the lowest calibration point relative standard deviation was less than 10.8%, indicating a good precision of the assay within the lowest concentration of interest. In conclusion, in this method article, we describe a simple, sensitive, and cost-effective 2D-LC/MS/MS method suitable for the routine analysis of a complex of steroid hormones allowing high analytical specificity and sensitivity despite minimal sample processing and short throughput times.
Keywords: QuEChERS method; reprodukovatelnost výsledků; steroidy; krevní plazma; multiplexed analysis of steroid hormones; tandemová hmotnostní spektrometrie; Chromatography, Liquid; 2D-LC/MS/MS; Humans; chromatografie kapalinová; Tandem Mass Spectrometry; Estradiol; lidé; Steroids; Plasma; Reproducibility of Results; two dimensional-liquid chromatography with tandem mass spectrometry; estradiol